PENGARUH DIGITALISASI PENGGUNAAN QRIS TERHADAP PENINGKATAN OMZET PADA UMKM DI KOTA MATARAM - Annisa Renda Lestari; Triana Lidona Aprilani; Muhammad Habibullah Aminy; Hery Astika Putra (Nusantara Hasana Journal, 2026)
This study aims to analyze the effect of digitalization through the use of the Quick Response Code Indonesian Standard (QRIS) on omzet growth among Micro, Small, and Medium Enterprises (MSMEs) in Mataram City. The research is motivated by the transition from cash-based to digital payment systems in response to technological advancement and the need for operational efficiency in business activities. QRIS is considered an innovation that enhances transaction efficiency, expands customer reach, and increases revenue for business actors. This research employed a quantitative method with an associative approach. The population consists of all MSMEs in Mataram city using QRIS, with the sample determined using the slovin formula at a 10% margin of error, resulting in 100 respondents. Data were collected through questionnaires using a likert scale, while data analysis included validity tests, reliability tests, classical assumption tests, simple linear regression analysis,t-test, and coefficient of determination (R2). The results indicate that the digital use of QRIS has a positive and significant effect on MSME omzet growth. This is supported by a t-value of 5.911, which is greater than the critical t-table value of 1.660, and a significance level of 0.000 (< 0.05). The coefficient of determination (R²) is 0.257, meaning that 25.7% of the variation in MSME profits is explained by the QRIS usage variable, while the remaining 74.3% is influenced by other factors. Therefore, the adoption of QRIS as a digital payment tool significantly contributes to increasing MSME profits in Mataram City.